Maternal Dietary Iodide Influences Turkey Embryo Thyroid Function - Christensen, V.L.; Davis, G.S. (International Journal of Poultry Science, 2004)
An experiment was designed to discover a mechanism for improved embryonic survival resulting from supplemental maternal dietary iodine. Commercial turkey breeder hens were fed diets containing 4 ppm supplemental iodide during a 20 wk egg production period (32 to 48 wk of age). Dietary iodide treatment depressed maternal blood thyroxine (T4) concentrations as the hens aged. Dietary iodide depressed maternal blood 3, 5, 3`- triiodothyronine (T3) levels at all times examined. The dietary iodide treatment increased embryonic blood concentrations of T4 at 25 to 28 d of incubation but depressed blood concentrations of T3 only at 27 d of incubation. In a second trial, the iodide treatment decreased embryonic T4 concentrations as well but in a time-dependent manner. When the hens were similarly fed additional iodide in Trial 2, no effects were noted in T3 concentrations. Iodide also accelerated the increase in embryo T4 concentrations and initiated earlier pipping in embryos compared with non-supplemented controls. The data indicate that embryo thyroid function during hatching is affected by the maternal dietary iodide in turkey dams even though the embryo develops outside the maternal body.